Manhattan : Letters from Prehistory - Cixous, Helene, 1937- (Book collections on Project MUSE., 2007)
Manhattan is the tale of a young French scholar who travels to the United States in 1965 on a Fulbright Fellowship to consult the manuscripts of beloved authors. In Yale University?s Beinecke Library, tantalized by the conversational and epistolary brilliance of a fellow researcher, she is lured into a picaresque and tragic adventure. Meanwhile, back in France, her children and no-nonsense mother await her return. A young European intellectual?s first contact with America and the city of New York are the background of this story. The experience of Manhattan haunts this labyrinth of a book as.